2001
DOI: 10.1093/treephys/21.17.1231
|View full text |Cite
|
Sign up to set email alerts
|

Site fertility and the morphological and photosynthetic acclimation of Pinus sylvestris needles to light

Abstract: Morphological and photosynthetic acclimation of current-year needles to canopy gradients in light availability (seasonal mean integrated quantum flux density, Q(int)) was studied in the temperate conifer, Pinus sylvestris L., at two sites of contrasting nutrient availability. The nutrient-rich site supported a monospecific P. sylvestris stand on an old-field. The trees were approximately 30 years old and 19-21 m tall. Mean foliar N and P contents (+/- SD) were 1.53 +/- 0.11% and 0.196 +/- 0.017%, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
110
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 80 publications
10
110
2
1
Order By: Relevance
“…Several researches into the morphological and physiological characteristics of needles (Niinemets et al, 2001(Niinemets et al, , 2002a(Niinemets et al, , 2002bNiinemets & Lukjanova, 2003) have revealed a strong dependence of the structure of the needles and shoots, the architecture of the shoot and crown geometry of the tree on the mineral composition of the soil. Needles from trees growing in nutrient-poor soil are thinner, narrower and with lower photosynthetic activity than needles from nutrient-rich sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researches into the morphological and physiological characteristics of needles (Niinemets et al, 2001(Niinemets et al, , 2002a(Niinemets et al, , 2002bNiinemets & Lukjanova, 2003) have revealed a strong dependence of the structure of the needles and shoots, the architecture of the shoot and crown geometry of the tree on the mineral composition of the soil. Needles from trees growing in nutrient-poor soil are thinner, narrower and with lower photosynthetic activity than needles from nutrient-rich sites.…”
Section: Discussionmentioning
confidence: 99%
“…It can grow in different climatic zones and soil conditions, both on sand and in bogs (Valk, 2005). The pines growing in various environmental conditions have differences in crown geometry, shoot architecture and the morphology of needles and shoots (Niinemets et al, 2001;2002a,b;Niinemets & Lukjanova, 2003). Numerous physiological and biochemical mechanisms are involved in the process of adaptation of plants to stressful and adverse conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Para Thomas y Martin (2012), los volátiles implican concentraciones de C que deben considerarse en las evaluaciones de dicho elemento en las especies forestales. Las hojas fueron el componente que ocupó el segundo lugar en la capacidad para almacenar C. Algunos autores argumentan que a pesar de tener menor cantidad de celulosa, las hojas son ricas en sustancias volá-tiles de alta concentración de C, por los procesos de fotosín-tesis que ahí ocurren (Niinemets, Ellsworth, Lukjanova & Tobias, 2001;Yerena et al, 2011). En contraste, el fuste y la rama tuvieron los valores más bajos, siendo similares entre sí.…”
Section: Resultsunclassified
“…They result mainly from the different susceptibility of those traits to environmental factors (Żelawski and Gowin 1966, Irvine et al 1998, Niinemets et al 2001, Urbaniak et al 2003. Paying special attention to these kind of aspects related to differentiation is crucial in our case -comparisons of populations originating from contrasting natural habitats.…”
Section: Discussionmentioning
confidence: 99%
“…The probable explanation for the observed differences lies in the different edaphic conditions in the places where they grow. The response of pine to extreme habitat conditions by producing shorter needles is known (Niinemets et al 2001;Urbaniak et al 2003), and such conditions are present in the case of the L1 population (poor and sandy dune soil). The influence of stress on pine in this population also manifests itself in high values of skewness (Tab.…”
Section: Discussionmentioning
confidence: 99%